Trilogi Persaudaraan yang Rukun Menurut Mazmur 133: Sebuah Nasehat, Dasar, dan Berkat - Bimo Setyo Utomo (JURNAL TEOLOGI GRACIA DEO, 2019)
Psalm 133 is known as one of the 15 Songs of Ascents and specifically this Psalm teaches about the importance of living in a harmonious brotherhood for the people of Israel in the context of God's people. In essence, Psalm 133 contains a trilogy which are: advice, foundation, and blessing regarding harmonious brotherhood. There are two depictions used by the Psalmist in this section to teach about harmony; first oil for the ordination of Imam Aaron and second, the dew from Mount Hermon. These two things were formulated by the psalmist to teach also the purpose of harmony, that God's blessings could be poured out on His people. God's blessing can be in the form of success, well-being or the tranquility of life in a long period of time that will certainly benefit the lives of His people. Abstrak Mazmur 133 dikenal sebagai salah satu dari 15 nyanyian ziarah (Songs of Ascents) dan secara spesifik Mazmur ini mengajarkan pentingnya hidup dalam persaudaraan yang rukun bagi orang Israel dalam konteks umat Allah. Secara garis besar, Mazmur 133 memuat sebuah trilogi yakni sebuah nasehat, dasar, dan berkat mengenai persaudaraan yang rukun. Ada dua penggambaran yang dipakai oleh Pemazmur dalam bagian ini untuk mengajarkan tentang kerukunan, yaitu minyak untuk penahbisan Imam Harun dan juga embun dari Gunung Hermon. Dua hal ini dirumuskan oleh pemazmur untuk mengajarkan pula mengenai tujuan dari sebuah kerukunan, yakni supaya berkat Allah dapat dicurahkan kepada umat-Nya. Berkat Tuhan dapat berupa keberhasilan, kesejahteraan atau kesentosaan hidup dalam kurun waktu yang panjang yang pasti bermanfaat bagi kehidupan umat-Nya.